ANALISIS PENERAPAN AKUNTANSI SYARIAH PADA PRODUK CICIL EMAS SESUAI PSAK 102 DI BANK SYARIAH INDONESIA KCP BARRU - Abdullah, Sri Mudita (Funds: Jurnal Ilmiah Akuntansi, Keuangan, dan Bisnis, 2024)
This study aims to explore the application of the gold installment product contract at BSI KCP Barru, the implementation of PSAK 102 at Bank Syariah Indonesia KCP Barru, and to analyze Sharia accounting related to the gold installment product based on PSAK 102 at Bank Syariah Indonesia KCP Barru. The researcher applied a type of field research, with a qualitative approach that is descriptive-analytical in nature. The analysis involved a detailed description of the research object through observation, interviews, and documentation methods. The data used in this research is categorized into two types, namely primary data and secondary data.The findings of this study indicate that the implementation of the gold installment product contract at Bank Syariah Indonesia KCP Barru has complied with the applicable regulations regarding gold ownership financing products for Bank Syariah Indonesia and sharia business units. At BSI KCP Barru, there is the implementation of a murabahah contract for the gold installment product, which can only be done through orders, with a payment system carried out in installments. BSI KCP Barru is still in the process of implementing the murabahah contract in accordance with PSAK 102 for this gold installment product, considering that the murabahah contract without orders has not yet been fully implemented. The implementation of sharia accounting on the gold installment product in accordance with PSAK 102 at Bank Syariah Indonesia KCP Barru is carried out by prioritizing the principles of accountability, justice, and truth. This has resulted in the gold installment financing product at BSI KCP Barru receiving a positive response from customers.